Separation of unauthorized occupation of land from other violations of land legislation - Сидоренко, В. В. (Theory and practice of jurisprudence, 2016)
This paper is devoted to the separation of unauthorized occupation of land as the land of the offense of misuse, unreasonable use of land and other types of offenses in land use and protection provided by law.